Oral Nucleos(t)ide Analogs Alone After Liver Transplantation in Chronic Hepatitis B With Preexisting rt204 Mutation. Issue 10 (October 2017) - Fung, James; Wong, Tiffany; Chok, Kenneth; Chan, Albert; Sin, Sui-ling; Cheung, Tan-to; Dai, Wing-Chiu; Ng, Kelvin; Ng, Kevin; Man, Kwan; Seto, Wai-kay; Lai, Ching-Lung; et al.
Abstract : Background: There is currently limited data regarding the use of oral antiviral therapy alone without hepatitis B immune globulin for chronic hepatitis B patients with preexisting lamivudine (LAM) resistance (LAM-R) undergoing liver transplantation. Methods: This is a cohort study determining the effectiveness and long-term outcome in this group of patients. Results: Fifty-seven consecutive chronic hepatitis B patients with preexisting rt204 LAM-R mutations or virological load refractory to LAM undergoing liver transplantation were included, with a median follow-up of 73 months. Fifty-five (96.5%) patients received a regimen that included the use of nucleotide analogs. The cumulative rate of hepatitis B surface antigen seroclearance at 1, 5, and 10 years was 82%, 88%, and 91%, respectively. At the time of transplantation, 39 (72%) patients had detectable hepatitis B virus (HBV) DNA, with a median of 4.5 log copies/mL. The cumulative rate of HBV undetectability was 91% at 1 year, increasing to 100% by 5 years. After 1 year of liver transplantation, over 90% of the patients had undetectable HBV DNA, and from 8 years onward, 100% had undetectable HBV DNA. The overall long-term survival was excellent, with a 12-year survival of 87%. There was no HBV-related graft loss, and no retransplantation or deaths due to HBV reactivation. Conclusion: Oral antiviral therapy alone without hepatitis B immune globulin is highly effective in preventing HBV reactivation and graft loss from recurrent hepatitis B after liver transplantation in patients with preexisting LAM resistance HBV. The long-term outcome was excellent, with survival of 87% at 12 years after transplantation, without any mortality related to HBV reactivation. Abstract : The authors of this series expand on their hepatitis B immunoglobulin-free prophylaxis approach after liver transplantation to confirm its effectiveness also in patients with preexisting lamivudine resistance to hepatitis B virus.